MANAGEMENT OF PAEDIATRIC EPIPHORA AND ITS SUCCESS RATE IN A TERTIARY EYE CARE CENTER - SUDESHNA ROY; MITA SAHA DUTTA CHOWDHURY; DEBALINA GHANTA; KUSUM KUMARI PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are to assess the children under 5 years of age presenting with epiphora and to institute proper treatment with regular follow-up to get an overview of treatment success. Methods: A prospective and non-randomized study was conducted on 518 eyes of 353 patients 165 (B/L) and 188 (U/L) that presented to us between April 2014 and April 2015. Informed consent was taken from parents. Institutional Ethical Committee approval was taken. The patients were followed up quarterly for 1st year to look for the resolution of signs and symptoms and if required quarterly till the resolution of the disease. Statistical analysis was done using Chi-square and Fisher’s exact test to test the difference in proportions. p<0.05 was denoted as statistically significant. Result: Congenital nasolacrimal duct obstruction (NLDO) was the most common cause of childhood epiphora - 76% (394/518) followed by trauma (iatrogenic and non-iatrogenic) seen in 18% (93/518), acquired NLDO in 4% (21/518) and punctual causes 2% (10/518). The overall treatment success rate was 82%, individual success rate: Sac Massage: 85.9%, probing: 73.95%, dacryocystorhinostomy (DCR): 72%, punctum surgery: 100%. Although with increasing age, success rate of massage and probing reduced. Conclusion: Sac massage is the best treatment in children till 1 year of age and probing is very effective till 3 years of age. Thus, early treatment prevents further chances of surgical intervention.